Pengaruh Metode Pembelajaran Eksprimen Aku Dan Kebutuhanku Terhadap Hasil Belajar IPAS Di Kelas IV Sekolah Dasar - Khusnah, Kharitsatul; Andjariani, Endang Wahju; Wulan, Budhi Rahayu Sri (Universitas Negeri Makassar, 2024)
This study aims to find out the influence of my learning method and my needs on the learning outcomes of grade IV elementary school students and to find out the number of questionnaire responses of grade IV elementary school students. This study uses quantitative research using a sampling technique of 40 students when conducting research at SD Negeri Lemahputro Sidoarjo. The results of the analysis of the experimental class pretest data obtained a significant value of 0.119 and the posttest of 0.421 more than (>) 0,05 This means that the data is distributed normally. The learning results of the control class pretest obtained a significant value of 0.131 and the posttest of 0.115 more than (>) 0.05, meaning that the data was normally distributed. The result of the t-count test is 3.048 with a t-table value of 1.812 which means that Ho is rejected and Ha is accepted so that in this study it can be said that the hypothesis is accepted. It can be concluded that there is an influence in the quasi-experimental research where this hypothesis uses the t-test formula with the calculation value of the hypothesis sig (2-tailed) > 0.05 so that it can be stated that there is an influence on my experimental learning method and my needs on the learning outcomes of science and science in grade IV of elementary school.